De/Constituting wholes : towards partiality without parts - Gragnolati, Manuele; Holzhey, Christoph F. E. (Cultural Inquiry, 2017)
How can the power of wholes be resisted without essentializing their parts? Drawing on different archives and methodologies, including aesthetics, history, biology, affect, race, and queer, the interventions in this volume explore different ways of troubling the consistency and stability of wholes, breaking up their closure and making them more dynamic. Doing so without necessarily presupposing or producing parts, an outside, or a teleological development, they indicate the critical potential of partiality without parts.